2018
DOI: 10.4103/jips.jips_167_18
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computerized tomography evaluation of incisive canal and anterior maxillary bone thickness for placement of immediate implants

Abstract: Purpose: Variation of dimensions of the nasopalatine canal and anterior maxillary bone thickness vary in relation to age, gender, edentulism, and ethnicity; thorough knowledge with regard to these landmarks is of vital importance prior to surgical procedures such as implant placement and local anesthesia in the anterior maxilla. Cone beam computerized tomography (CBCT) aids in accurate treatment planning in such situations. Subjects and Methods: A total of 300 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
(72 reference statements)
3
15
1
2
Order By: Relevance
“…Alveolar bone thickness defines the occlusal-gingival position of the implant, and it is vital for long-term soft tissue stability [40]. Estimation of the horizontal alveolar ridge dimension at different levels is very important from the aspect of immediate implant placement, since this dimension is larger in the apical than in the crestal part, to assess whether a more apical implant position would provide greater bone thickness in this critical region for the implant placement [41].…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar bone thickness defines the occlusal-gingival position of the implant, and it is vital for long-term soft tissue stability [40]. Estimation of the horizontal alveolar ridge dimension at different levels is very important from the aspect of immediate implant placement, since this dimension is larger in the apical than in the crestal part, to assess whether a more apical implant position would provide greater bone thickness in this critical region for the implant placement [41].…”
Section: Discussionmentioning
confidence: 99%
“…Gender wise no statistically significant difference was seen in mesiodistal dimension of IF; however, the mean diameter was greater in males. Panda et al ,[ 2 ] Rao et al ,[ 17 ] Khojastepour et al ,[ 18 ] and Gopal and Kapoor[ 19 ] also reported similar significant differences. Age-wise mesiodistal dimension was increasing with increase in age group, and difference was statistically highly significant ( P = 0.007).…”
Section: Discussionmentioning
confidence: 67%
“…However, in the study conducted by Panda et al , the average distance was found to be 13.81 (±2.05) mm, with statistical differences gender wise and age wise. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations